CEE labour markets – homogeneity or diversity? - Rollnik-Sadowska, Ewa; Jarocka, Marta (Technological and Economic Development of Economy, 2021)
The aim of the article is to assess real changes taking place on CEE labour markets over the last fifteen years, taking into account as the initial point of analysis – 2004, i.e. the moment of extension of the EU by the first CEE countries and as a final point of analysis – 2019. The research was conducted in two stages. The authors made comparisons with the use of the TOPSIS method, which allowed for creating rankings of CEE countries in terms of labour market situation in the analysed years. The second stage of the study involved the analysis of relations between employment and GDP by an estimation of the multiple regression model. The conducted analysis proves that CEE countries are diversified when it comes to the labour market situation. These countries are also characterized by significant dynamics of changes in the labour market.First published online 05 July 2021